PERMOHONAN PIDANA TERHADAP PNS YANG MELAKUKAN TINDAKAN PIDANA NARKOBA: (Nomor Studi Kasus : 109/109/Pid.Sus/2016/PN. Pmn dan Nomor Kasus : 104/Pid.Sus/2018/PN.Pmn) - Harto, Edi; Rosadi, Otong; Fahmiron, Fahmiron (Program Magister Ilmu Hukum Universitas Ekasakti, 2020)
The abuse ofnarcoticsinPariamancityisnotonlydoneby publicbutalsoby civil servant.The narcoticscrime are done by civilservantinPariamancityisabuse of narcotics Part Ifor theirselves asmentionedin theLaw Number 35Year 2009 about Narcotics.Forthis action,thePariamanCourtgivespunishmentnamelyasprisoner forone yeartotheaccuses.The problemsinthisstudyare:First,howaboutthe implementationofcriminalsanctionto civilservantwhodoesthenarcoticcriminal law in the cases 109/Pid.Sus/2016/PN.Pmn and the cases number:104/Pid.Sus/2018/PN.Pmn?Second,howthejudge’sconsiderationinapplyingthecriminalsanctiontothecivilservantwhodoesthenarcoticcriminallawinthecases109/Pid.Sus/2016/PN.Pmn the cases number: 104/Pid.Sus/2018/PN.Pmn?This research is legal research with analytical descriptive specifications. The approachusedisanormativejuridicalapproachandsupportedbyanempirical juridicalapproach.Thedatasourcesusedaresecondarydatawithdatacollection techniquesintheformof documentstudiesandfieldstudiesthrough interviews.Then the data is analyzed qualitatively and described indescriptiveanalytical form. Keyword : Criminal, Civil Servant, Narcotics